Potential use of waste eggshells in cement-based materials: A bibliographic analysis and review of the material properties - Yang, Dawei; Zhao, Jiahui; Ahmad, Waqas; Nasir Amin, Muhammad; Aslam, Fahid; Khan, Kaffayatullah; Ahmad, Ayaz (Construction & building materials, 2022)
[Display omitted] •Quantitative assessment of the present research is performed by scientometric analysis.•Mechanical and durability performance of composites containing ESP are discussed.•Inconsistent results have been noticed with the addition of ESP in cementitious materials.•The incorporation of ESP in cementitious materials will promote eco-friendly construction. The disposal of waste eggshells results in severe environmental and human health interests. Eggshells in powder form have the potential to be utilized in cementitious materials as a partial substitute for cement and fine aggregate. Hence, an environmentally friendly construction material can be produced with the use of eggshell powder. In order to assess the diverse parameters of the available literature on the use of eggshell powder in cementitious materials, a scientometric analysis approach was employed in this study. In addition, the mechanical properties, including slump, density, compressive, split-tensile, and flexural strength, and durability properties of the cementitious materials containing eggshell powder, are discussed. The various factors of eggshell powder affecting the performance of cementitious materials are highlighted, as well as their limitations and possible solutions. The three main influencing factors are CaO content, eggshell powder particle size, and replacement level of eggshell powder. The use of eggshell powder having a higher CaO content and finer particle size enhances the performance of cementitious materials, especially when used along with the pozzolanic materials (fly ash, silica fume, nano-silica, etc.). However, some studies reported the negative impact of eggshell powder on material performance. This study concluded that the utilization of eggshell powder in cementitious materials is beneficial when used in the replacement ratio of up to 25% cement/fine aggregate. The research on the present topic is in the initial stages, and further in-depth investigations are essential to better interpret the impact of eggshell powder on material properties and its applications in construction materials. Moreover, modification of the grinding process and calcination of eggshells is suggested to achieve eggshell powder with finer particle size and higher CaO content.